2010
DOI: 10.1007/s00436-009-1703-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Giardia duodenalis isolates from domestic ferrets

Abstract: Giardia duodenalis is a pathogen that has been found in a variety of mammals, including humans, and consists of host-specific (assemblages C, D, E, F, and G) and zoonotic (assemblages A, B) genetic groups. Ferrets are popular pets, and they, like humans, are hosts to this pathogen. The genetic characteristics of the Giardia population in ferrets are unclear because only one ferret isolate has been genotyped. To develop a more complete picture of the genetic characteristics of the Giardia population in domestic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…The presence of assemblage A has been reported previously in ferrets (Mustela putorius furo Linnaeus) in Japan (Abe et al 2010). …”
Section: Discussionsupporting
confidence: 69%
“…The presence of assemblage A has been reported previously in ferrets (Mustela putorius furo Linnaeus) in Japan (Abe et al 2010). …”
Section: Discussionsupporting
confidence: 69%
“…In a more recent study from Italy, however, all 20 isolates characterized belonged to assemblage E (285). In other domestic pets, assemblage B was found in one rabbit each in China and Sweden (154,249), and assemblage A was found in three ferrets in Japan (3,4). MLG analysis of the three ferret isolates suggested that they might belong to two host-adapted assemblage A subtypes (4).…”
Section: Molecular Epidemiology Of Giardiasis Molecular Epidemiology mentioning
confidence: 99%
“…One of the main tools to study genetic variation of different populations of Giardia is the molecular characterization based on multiple loci. Recent molecular analysis of Giardia isolates at the glutamate dehydrogenase (gdh), triose phosphate isomerase (tpi), and beta-giardin (bg) genes indicate a high degree of genetic variability within both assemblages A and B, and subassemblages have been described within them (Abe et al 2010;Cacciò et al 2008;Levecke et al 2009;Wielinga and Thompson 2007). These studies may enhance our understanding of the different pathways of transmission and the importance of animals as reservoirs for human giardiasis.…”
Section: Introductionmentioning
confidence: 96%
“…G. lamblia, Giardia intestinalis), G. agilis, G. muris, G, psittaci, G. ardeae, and G. microti, distinguished on the basis of the morphology and ultrastructure of their trophozoites (Sprong et al 2009). In any case, it is well established that G. duodenalis is a species complex composed of at least seven distinct genetic groups, referred as assemblages A to G (Abe et al 2010;Beck et al 2011;Lasek-Nesselquist et al 2009;Lebbad et al 2010).…”
Section: Introductionmentioning
confidence: 99%